Harpactea konradi, a new spider species from Bulgaria, (Araneae, Dysderidae) - Lazarov, Stoyan (Zootaxa, 2009)
A new spider species, Harpactea konradi, is described and illustrated from specimens collected in South Bulgaria (Eastern Rhodopes). The male palps of the species resemble those of Harpactea srednagora Dimitrov & Lazarov, 1999, in having the biforcate embolus, but this is thicker and more massive, and the conductor is tighter and longer. It is known only from the type locality.